Australian News Photography and Contested Images of Famine in Indonesian-occupied East Timor - Hearman, Vannessa (Taylor & Francis, 2023)
The Indonesian invasion of East Timor in December 1975 and subsequent military operations to suppress the East Timorese resistance led to widespread displacement and famine in 1977–79. With Indonesia restricting access to East Timor during the operations, a set of photographs of famine-afflicted children, taken by Australian journalist, Peter Rodgers and published in metropolitan daily newspapers in Melbourne and Sydney in November 1979 triggered renewed debate about conditions in the territory. This article traces the production and circulation of the photographs by a range of image brokers, those working in the media and those campaigning for East Timor’s independence. The Rodgers photographs are now recognised as iconic and foundational in the collection of images used in the independence campaign. However, the history of the Rodgers photographs and the discourses that developed around them demonstrate the multiple interpretations and problems that arise in representations of famine through photographs.